2009
DOI: 10.1097/jsm.0b013e3181b544f6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humeral Torsion on Interpretation of Posterior Shoulder Tightness Measures in Overhead Athletes

Abstract: Although limb differences in clinical indicators of posterior tightness exist in healthy overhead athletes, these measures appear to be influenced by humeral torsion rather than soft tissue tightness. Once torsion is accounted for, the limb differences observed clinically were minimal in healthy overhead athletes. When possible, accounting for humeral torsion when interpreting clinical measures of posterior shoulder tightness may aid in treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
144
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(153 citation statements)
references
References 29 publications
8
144
1
Order By: Relevance
“…The previously discussed factors that influence the joint torques and stress on the shoulder-stabilizing musculature and posterior capsule could also influence the development of humeral retrotorsion and thus the interpretation of rotational ROM measures. 16 In addition, the female growth spurt is generally shorter than that of the male, 28 allowing a longer period of time for the open epiphyseal plates of the male to be manipulated by humeral torques and for humeral retrotorsion to develop. Finally, as we learned from our experience with youth baseball teams, the majority of children participating on these teams are expected to pitch at some point.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The previously discussed factors that influence the joint torques and stress on the shoulder-stabilizing musculature and posterior capsule could also influence the development of humeral retrotorsion and thus the interpretation of rotational ROM measures. 16 In addition, the female growth spurt is generally shorter than that of the male, 28 allowing a longer period of time for the open epiphyseal plates of the male to be manipulated by humeral torques and for humeral retrotorsion to develop. Finally, as we learned from our experience with youth baseball teams, the majority of children participating on these teams are expected to pitch at some point.…”
Section: Discussionmentioning
confidence: 99%
“…The additional stress at the shoulder from pitching in games and practice may be another reason why humeral retrotorsion is greater in baseball players. 29 Previous authors 16,30,31 have identified the osseous component of humeral retroversion as a major contributor to ROM measures and suggested using a corrected-ROM measure to better assess the soft tissue restriction that is present. This adjustment has been proposed to isolate the total-ROM alterations in the shoulder that are attributed to soft tissue contracture or lengthening, as opposed to the traditional thought that all variations in ROM are caused by soft tissue differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations